Implementation challenges of sustainability practice in public procurement in Bangladesh: role of CPTU - Prince, Muhammad Ali (Brac University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2019.